Antara Ada dan Tiada: Studi Terhadap Tingkat Kehadiran dan Keaktifan Mahasiswa dalam Pembelajaran Online di Era Covid-19 - Soni Ariawan (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2022)
The study aims to analyze the level of students’ attendance and interaction as well the availability of internet access during online learning in the era of Covid-19 pandemic. The case study is conducted at the English Language Education Study Program, Faculty of Education and Teacher Training State Islamic University of Mataram. This research is a part of quantitative research design with surveys. The researcher developed a set of questionnaire in Google Form and shared it to the students via WhatsApp group. 215 students participated in this study. It was found that most of the students attended the class throughout the meetings, but it could not be concluded that they participated during the class from the beginning till the end of the meeting. The causes were by the lack of internet access, instability of signal as well as the availability of the devices. The phenomenon showed that students exist in the class but do not exist. A successful learning occurs when interaction and communication run smoothly among students and teachers.